Physical Properties of Jakekur Project of Osmanabad District (M.S.), India - Ugale, B.J. (Recent Research in Science and Technology, 2011)
Present paper deals with study of physical factors like water temperature (Temp), pH, transparency, turbidity, Total Dissolved Solids (TDS), and conductivity (EC) of Jakekur project (Reservoir).